X+(x+7.8)=726.2

Simple and best practice solution for X+(x+7.8)=726.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x+7.8)=726.2 equation:


Simplifying
X + (x + 7.8) = 726.2

Reorder the terms:
X + (7.8 + x) = 726.2

Remove parenthesis around (7.8 + x)
X + 7.8 + x = 726.2

Reorder the terms:
7.8 + X + x = 726.2

Solving
7.8 + X + x = 726.2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-7.8' to each side of the equation.
7.8 + X + -7.8 + x = 726.2 + -7.8

Reorder the terms:
7.8 + -7.8 + X + x = 726.2 + -7.8

Combine like terms: 7.8 + -7.8 = 0.0
0.0 + X + x = 726.2 + -7.8
X + x = 726.2 + -7.8

Combine like terms: 726.2 + -7.8 = 718.4
X + x = 718.4

Add '-1x' to each side of the equation.
X + x + -1x = 718.4 + -1x

Combine like terms: x + -1x = 0
X + 0 = 718.4 + -1x
X = 718.4 + -1x

Simplifying
X = 718.4 + -1x

See similar equations:

| n-38=50 | | 8+2*(-8)-6= | | -17+5=-4(x+1) | | x+22=3x+6 | | x^2/ | | 8(2c+4)=0 | | 84=4v-2(X-3)-3x | | 160+170+400+x=1000 | | 128=2n+8(n+6v) | | 5/9d=9/4 | | 11x+3=10x+3 | | (3/7)x-1=(2/3)(6x-2) | | (3/7)x-1=(⅔)(6x-2) | | 83=2(-6b+1)-3 | | (3/7)x-1=(2/ | | 11k=13t−7k/2t | | 1+Log[5](-4x)=3 | | 544=-5n-8(7n-7) | | (3z-5)(7-z)=0 | | 2/3y-6=10 | | 3x-4(-2x-5)=2x-3 | | 5x^2+6-51=0 | | h-4+1=3 | | 8(3x-5)=-64 | | ln(17+2x)=2ln(x+1) | | 7/7=3 | | -2x-5(4x+3)=3x | | 26=10h/18 | | 11.5x+12=161.50 | | 3(-2y)+7y=1 | | 5t=56 | | c=12+11.5t |

Equations solver categories